The Influence of Transformational Leadership Style and Organisational Culture on Employee Performance Mediated by Organisational Commitment - Mahmud Mahmud; Ega Saiful Subhan; Paroli Paroli (Universitas Mercu Buana, 2025)
Objective: This study aims to analyze the influence of transformational leadership and organizational culture on employee performance, with organizational commitment serving as a mediating variable at CV Aquaku Jaya Bersama in Dompu Regency, West Nusa Tenggara.Methodology: This study uses a quantitative causal approach with a population of 78 employees. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 3 software. The analysis procedure included measurement evaluation, structural modelling, and direct and indirect hypothesis testing.Findings: The results showed that transformational leadership did not directly influence employee performance but had a positive and significant effect on organisational commitment. Organisational culture has a positive and significant influence on both organisational commitment and employee performance. In addition, organisational commitment positively influenced employee performance and substantially mediated the relationship between transformational leadership and employee performance. However, organisational commitment did not mediate the relationship between organisational culture and employee performance.Conclusion: This study emphasises the importance of building organisational commitment to improve employee performance through leadership and work culture approaches.